Electoral Systems and Economic Growth: What is the Importance of the Proportionality Degree? - M. Rosaria Alfano; A. Laura Baraldi (Economics and Econometrics Research Institute (EERI), 2014)
Previous empirical studies analysing the effect of electoral systems on growth lack unanimous answers as they miss-specify mixed systems in the empirical setting, that is, they neglect to consider the proportionality degree of mixed electoral systems. This work supplies the missing answers by properly distinguishing the three types of electoral rules using a proportionality degree index, that is, the Gallagher index. We estimate a non-linear relationship between the Gallagher proportionality index and the per capita GDP growth using cross-country panel data. Our findings show that the proportionality degree is significant for growth; mixed systems (characterised by an intermediate level of proportionality), combining the different advantages of both proportional and plurality systems, solve the problem of the accountability-responsiveness and the political-government instability trade-offs. As a consequence, they reach relatively higher growth rates with respect to more “extreme” electoral rules.
Keywords: C23; D72; H1; 330; Economic Growth; Electoral System; Proportionality index